Peningkatan Partisipasi Masyarakat Sadar Wisata dan Aksi Sosial di Desa Hutaginjang, Kec. Muara, Kabupaten Tapanuli Utara - Harisan Boni Firmando (Jurnal Abdi Mas Adzkia, 2022)
The success of the tourism industry is supported by three elements, namely people, place and time. Humans as human actors in tourism activities, place as an area covered by tourism activities and time as a period of time used in tourist trips while staying in tourist destinations. It was found that many people do not have awareness of tourism potential and care about the environment, so that the level of community participation in the development of tourist destinations is still low. This service uses an empowerment perspective with the ABCD (Asset Based Community Development) method to increase community participation, so that tourist destinations in Hutaginjang Village can be developed and efficient for the community. This service seeks to empower the community by providing various information about increasing participation in tourist destinations through counseling, thus opening the paradigm of the community in managing and developing tourism objects and making persuasive efforts in the form of social action activities, social action activities such as socializing the 5 M Movement, distributing masks and distributing books. The results of this service can be seen from the beautiful village area and increased community participation in the development of tourist destinations.